THE INFLUENCE OF SERVICE QUALITY, PRICE, LOCATION ON PURCHASING DECISIONS (Consumer Studies RM. Coto Makassar 3 &; Seafood in Takalar County) - Muh. Asbar (Journal of Accounting Issues, 2023)
Muh. Asbar, Sohra Syam, Wisnu Tri Sardi. 2023. The purpose of the study is to evaluate how RM's buying decision is affected by service quality, cost, and location. seafood from Takaral Regency and Kotoma Kassar 3. There were one hundred buyers or consumers present. In this work, the transverse sampling approach was employed in conjunction with the Lemeshow equation as a sample methodology. The information used is the survey's raw data. Utilize multiple regression analysis to analyze your data. Using the SPSS version 25 program, examine the survey's results. The computed value of 3.590 is more than Table 1.984 since the outcomes of processing QoS data have a substantial influence on purchasing decisions, and the crucial value of 0.001 is less than 0.05 (0.0010.05) because of this. If the calculated value is -0.930 (less than Table 1.984) and the significant value is 0.355 and more than or 0.05 (0.3550.05), the processing of price data has no impact on the purchase decision. The outcome of processing location data for a calculated value of 1.080 less than ttable 1.984 and a significant value of 0.283 (0.2830.05) larger than or 0.05 also suggests that location has no bearing on consumers' purchasing decisions.